2020
DOI: 10.1002/bmc.4732
|View full text |Cite
|
Sign up to set email alerts
|

A review of the bioanalytical methods for the quantitative determination of capecitabine and its metabolites in biological matrices

Abstract: The bioanalysis of the oral anticancer drug capecitabine and its metabolites has been investigated extensively over the past years. This paper reviews methods for the bioanalysis of capecitabine and its metabolites. The focus of this review will be on sample pre‐treatment, chromatography and detection. Furthermore, the choice of standards and analytical problems encountered during analysis of capecitabine and its metabolites in biological matrices will be discussed. The major challenges in the bioanalysis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Zufía, Aldaz, and Giráldez (2004) reported the use of a mixture of ethyl acetate and acetonitrile (4:1, v/v) after sample acidification with orthophosphoric acid to simultaneously extract capecitabine, 5 -DFUR (5 -deoxy-5-fluorouridine), 5-FU (5-fluorouracil), and 5-FUH2 (5,6-dihydro-5-fluorouracil) from plasma. A similar extraction method is also reported using LLE with a mixture of ethyl acetate and acetonitrile as the extractant (8:3, v/v) [6]. Piórkowska et al (2014) have reported a similar extraction method using a mixture of ethyl acetate and acetonitrile (4:1, v/v) but without sample acidification.…”
Section: Clinical Applications 21 Anticancer Drugsmentioning
confidence: 89%
See 1 more Smart Citation
“…Zufía, Aldaz, and Giráldez (2004) reported the use of a mixture of ethyl acetate and acetonitrile (4:1, v/v) after sample acidification with orthophosphoric acid to simultaneously extract capecitabine, 5 -DFUR (5 -deoxy-5-fluorouridine), 5-FU (5-fluorouracil), and 5-FUH2 (5,6-dihydro-5-fluorouracil) from plasma. A similar extraction method is also reported using LLE with a mixture of ethyl acetate and acetonitrile as the extractant (8:3, v/v) [6]. Piórkowska et al (2014) have reported a similar extraction method using a mixture of ethyl acetate and acetonitrile (4:1, v/v) but without sample acidification.…”
Section: Clinical Applications 21 Anticancer Drugsmentioning
confidence: 89%
“…Piórkowska et al (2014) have reported a similar extraction method using a mixture of ethyl acetate and acetonitrile (4:1, v/v) but without sample acidification. Acidification was not deemed necessary because the assay was developed to determine only capecitabine concentrations (no metabolites) [6].…”
Section: Clinical Applications 21 Anticancer Drugsmentioning
confidence: 99%
“…The high hydrophilicity of 5-FU and its active metabolites hinders their isolation from biological matrices. The high aqueous solubility and the low solubility to organic solvents result in extraction difficulties [ 48 , 49 ]. The most applied techniques to remove interfering endogenous substrates, namely liquid-liquid extraction (LLE), solid-phase extraction (SPE) and protein precipitation (PP), have been thoroughly reviewed [ 49 ].…”
Section: Electrochemical Sensors – Advantages and Limitationsmentioning
confidence: 99%
“…Numbers of analytical methods such as RP-HPLC, LC-MS, UV-Visible spectrophotometric method, stability-indicating RP-HPLC methods have been reported for estimation of capecitabine [8][9][10][11][12][13][14][15][16][17][18][19][20] . But there was no stability-indicating UV-visible spectrophotometry method was found reported by which capecitabine can be estimated independently to degradation products formed in different stress conditions such as hydrolysis, photolysis, oxidation, dry heat degradation etc.…”
Section: Figure I: Chemical Structure Of Capecitabinementioning
confidence: 99%